2013
DOI: 10.1002/ar.22731
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Distal Drift in Rat Molars Contributes to Acellular Cementum Formation

Abstract: Occlusal forces may induce the physiological teeth migration in humans, but there is little direct evidence. Rat molars are known to migrate distally during aging, possibly caused by occlusal forces. The purpose of this study was to determine if a reduction in occlusion would decrease teeth migration and affect associated periodontal structures such as cementum. To reduce occlusal forces, the right upper first molar (M1) in juvenile rats was extracted. The transition of the position of upper second molar (M2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Penyerapan akar gigi hanya berlaku kepada 5-10% daripada subjek yang tidak pernah mendapat rawatan ortodontik (Consolaro & Furquim 2014). Hal ini berlaku kerana gigi mengalami aliran distal (mesial drift) oleh daya oklusal (Tsuchiya et al 2013). Insisor tengah maksila mempunyai peratusan tertinggi untuk berlakunya tahap penyerapan akar gigi yang teruk, diikuti dengan insisor lateral maksila dan insisor lateral mandibel (Maués et al 2015).…”
Section: Perbincanganunclassified
“…Penyerapan akar gigi hanya berlaku kepada 5-10% daripada subjek yang tidak pernah mendapat rawatan ortodontik (Consolaro & Furquim 2014). Hal ini berlaku kerana gigi mengalami aliran distal (mesial drift) oleh daya oklusal (Tsuchiya et al 2013). Insisor tengah maksila mempunyai peratusan tertinggi untuk berlakunya tahap penyerapan akar gigi yang teruk, diikuti dengan insisor lateral maksila dan insisor lateral mandibel (Maués et al 2015).…”
Section: Perbincanganunclassified
“…In clinical cases, this measurement may be affected by traumatised teeth, or impossible if the maxillary carnassials are missing. Although dental drift–the movement of remaining teeth following tooth loss–has not been documented in dogs, it does occur in people, horses 25,26 and rats 27 . This may affect the applicability of our equation in the wider population of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that rat molars physiologically migrate in the distal direction with aging 22 23 and occlusal forces play an important role in this migration. 24 A split-mouth design was used for dental model measurements because of the physiological distal drift of the molars, physiological growth of the snout, forward movement of the incisors, and the possible distal tipping of the incisors used as anchorage. 25 Compensation for these effects was performed by measuring the incisor–molar distances on the experimental and control sides.…”
Section: Discussionmentioning
confidence: 99%